Trauma at School: The Impacts of Shootings on Students' Human Capital and Economic Outcomes - Marika Cabral; Bokyung Kim; Maya Rossin-Slater; Molly Schnell; Hannes Schwandt (Institute of Labor Economics (IZA), 2020)
A growing number of American children are exposed to gun violence at their schools, but little is known about the impacts of this exposure on their human capital attainment and economic well-being. This paper studies the causal effects of exposure to shootings at schools on children's educational and economic outcomes, using individual-level longitudinal administrative data from Texas. We analyze the universe of shootings at Texas public schools that occurred between 1995 and 2016, and match schools that experienced shootings with observationally similar control schools in other districts. We use difference-in-differences models that leverage within-individual and across-cohort variation in shooting exposure within matched school groups to estimate the short- and long-run impacts of shootings on students attending these schools at the time of the shooting. We find that shooting-exposed students have an increased absence rate and are more likely to be chronically absent and repeat a grade in the two years following the event. We also find adverse long-term impacts on the likelihood of high school graduation, college enrollment and graduation, as well as employment and earnings at ages 24-26. Heterogeneity analyses by student and school characteristics indicate that the detrimental impacts of shootings are universal, with most sub-groups being affected.
Keywords: I24; I31; J13; 330; childhood trauma; human capital development; school shootings